Risk of Major Abdominal Surgery in an Asian Population-based Crohn's Disease Cohort. Issue 11 (November 2015) - Pandey, Anuradha; Salazar, Ennaliza; Kong, Christopher S. C.; Lim, Wee Chian; Ong, Jeannie; Ong, David E. H.; Ong, Christina; Aw, Marion; Wee, Eric; Chuah, Sai Wei; Tan, Valerie; Tay, Wei Lin; et al.
Abstract : Background: Crohn's disease (CD) is increasing in incidence and prevalence in Asia, but there is a paucity of population-based studies on risk factors for surgery in Asian patients with CD. This will be useful to identify patients who may benefit from top-down treatment. This study describes the rates of abdominal surgery and identifies associated risk factors in Singaporean patients with CD. Methods: This was a retrospective observational study. The medical records of Singaporeans diagnosed with CD from 1970 to 2013 were reviewed from 8 different hospitals in Singapore. The cumulative probability of CD-related abdominal surgery was estimated using the Kaplan–Meier method. The logistic regression model was used to assess associations between independent risk factors and surgery. Results: The cohort of 430 Singaporean patients with CD included 63.5% Chinese, 11.9% Malay, and 24.7% Indians, with a male to female ratio of 1.6; median follow-up was 7.3 years (range, 2.9–13.0 yr) and median age at diagnosis 30.5 years (range, 19.5–43.7 yr). One hundred twelve patients (26.0%) required major abdominal surgery: the cumulative risk of surgery was 14.9% at 90 days, 21.2% at 5 years, 28.8% at 10 years, 38.3% at 20 years, and 50.6% at 30 years from diagnosis. Of the surgical patients, 75.0% were Chinese, 10.7% Malays, and 14.3% Indians; 21.4% underwent surgery for inflammatory disease, 40.2% for stricturing disease, and 38.4% for penetrating disease. Age at diagnosis (A2 17–40 yr, OR: 2.75, 95% confidence interval [CI], 1.14–7.76), ileal disease (L1 location, OR: 2.35, 95% CI, 1.14–5.0), stricturing (B2 OR: 6.09, 95% CI, 3.20–11.8), and penetrating behavior (B3 OR: 21.6, 95% CI, 9.0–58.8) were independent risk factors for CD-related abdominal surgery. Indian patients were less likely to require surgery (OR: 0.40, 95% CI, 0.19–0.78). Conclusions: Age at diagnosis, L1 location, B2, and B3 disease behavior are independent risk factors for abdominal surgery. Interestingly, despite a higher prevalence of CD in Indians, a smaller proportion of Indian patients required surgery. These findings suggest that both environmental and genetic factors contribute to the risk of surgery in Asian patients with CD. Abstract : Article first published online 1 August 2015.